2018
DOI: 10.1038/s41598-018-27058-0
|View full text |Cite
|
Sign up to set email alerts
|

A single cell high content assay detects mitochondrial dysfunction in iPSC-derived neurons with mutations in SNCA

Abstract: Mitochondrial dysfunction is implicated in many neurodegenerative diseases including Parkinson’s disease (PD). Induced pluripotent stem cells (iPSCs) provide a unique cell model for studying neurological diseases. We have established a high-content assay that can simultaneously measure mitochondrial function, morphology and cell viability in iPSC-derived dopaminergic neurons. iPSCs from PD patients with mutations in SNCA and unaffected controls were differentiated into dopaminergic neurons, seeded in 384-well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 79 publications
1
33
0
3
Order By: Relevance
“…was also reported for SNCA trp and SNCA A53T mesDA neurons (Little et al, 2018). As these observations hint towards a profound disturbance of mitochondrial function in familial forms of PD, several groups consequently investigated effects of PD risk factors on mitochondrial redox homeostasis and found increased levels of mitochondrial reactive oxygen species (ROS) in mesDA neurons carrying polymorphisms in LRRK2, DJ-1, PINK1, PRKN and SNCA (Burbulla et al, 2017;Chung et al, 2016;Ryan et al, 2013;Su & Qi, 2013;Suzuki et al, 2017), as well as in NPCs with SNCA trp and OPA1 variants (Flierl et al, 2014;Iannielli et al, 2018).…”
Section: Disrupted Mitochondrial Dynamics and Mitophagysupporting
confidence: 70%
See 1 more Smart Citation
“…was also reported for SNCA trp and SNCA A53T mesDA neurons (Little et al, 2018). As these observations hint towards a profound disturbance of mitochondrial function in familial forms of PD, several groups consequently investigated effects of PD risk factors on mitochondrial redox homeostasis and found increased levels of mitochondrial reactive oxygen species (ROS) in mesDA neurons carrying polymorphisms in LRRK2, DJ-1, PINK1, PRKN and SNCA (Burbulla et al, 2017;Chung et al, 2016;Ryan et al, 2013;Su & Qi, 2013;Suzuki et al, 2017), as well as in NPCs with SNCA trp and OPA1 variants (Flierl et al, 2014;Iannielli et al, 2018).…”
Section: Disrupted Mitochondrial Dynamics and Mitophagysupporting
confidence: 70%
“…In summary, alterations in mitochondrial morphology were repeatedly shown not only for LRRK2 variants (Su & Qi, ) but also for mutants of SNCA trp/A53T PINK1, PRKN and OPA1 (Chung et al., ; Iannielli et al., ; Imaizumi et al., ; Little et al., ; Shaltouki et al., ; Zanon et al., ).…”
Section: Pd‐associated Lrrk2 Variants In Ipsc‐based Disease Modelingmentioning
confidence: 90%
“…inhibitor. Interestingly we have used a similar high-content assay to detect decreased mitochondrial membrane potential in iPSC-derived dopaminergic neurons from patients with Parkinson's disease (Little et al, 2018). This suggests that such an assay could be used to identify potential novel therapies for Parkinson's disease too.…”
Section: Testing Candidate Drugsmentioning
confidence: 95%
“…A high-throughput analysis showed that SNCA triplication iPSC-induced DA neurons harbored mitochondrial morphological changes and a decrease in mitochondrial membrane potential [33]. A transcriptomic analysis of purified SNCA triplication iPSCderived DA neurons revealed perturbation of gene expression associated with mitochondrial function.…”
Section: Mitochondrial Toxicitymentioning
confidence: 99%